Revitalizing Regional Languages with Technology: Development of AI and Gamification-Based Language Learning Applications - Firdaus, Muhammad Ridwan; Wahyuni, Erna; Khan, Jamil; Zahir, Roya (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
The rapid decline of regional languages poses a significant challenge to cultural preservation and linguistic diversity. As globalization and digitalization continue to spread, regional languages are at risk of being overshadowed by dominant languages. This research explores the potential of technology, particularly artificial intelligence (AI) and gamification, to revitalize regional languages by enhancing language learning applications. The study aims to develop and evaluate an AI-driven, gamified language learning application designed to promote the acquisition and preservation of regional languages. The research employs a mixed-methods approach, combining the development of the language learning application with usability testing and user feedback. The application integrates AI to provide personalized learning experiences and uses gamification elements to increase engagement and motivation. The effectiveness of the application was tested through pilot studies with users from different age groups, focusing on language retention, engagement, and user satisfaction. The results show that the AI and gamification-based application significantly improved language retention and engagement among participants. Users reported higher motivation and enjoyment compared to traditional language learning methods, and the application was particularly effective in making learning more interactive and appealing for younger audiences. This study concludes that integrating AI and gamification into language learning applications can play a pivotal role in revitalizing regional languages, providing a scalable and engaging solution for preserving linguistic heritage.